An unusual case of spontaneous bacterial myositis. Issue 594 (April 1975) - Williams, R. H. P.; Thomas, P.
Abstract : A further report of spontaneous bacterial myositis occurring in the British Isles is recorded. The case is unusual because both calf muscle compartments were simultaneously affected, and unique in that surgical decompression was required to prevent impending limb ischaemia.